Perancangan Sistem Informasi Penilaian Siswa Berbasis Android Di Smp Negeri 1 Sungai Mandau - Rahmat Wibowo; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Education is something that helps for the progress of the nation. Assessment is a process carried out to make decisions using information from learning outcomes. One of the problems at SMPN 01 Sungai Mandau, the assessment was carried out using paper so that there were many mistakes. This problem can be overcome by creating an information system that can help the teacher assessment process to make it faster and safer. Making this information system requires several important components, namely in the form of Java and XML programming languages for the Android system, while PHP, HTML, and CSS for web systems. The method that I use to create this information system is the waterfall method using the MySQL database. The author's testing is done by using usability testing and black-box testing methods. The results of the information system can make it easier for teachers to fill in student scores, students or parents to see the results of grades, sponsors to manage scholarships and IT employees in managing grades. Keywords: School, Assessment, Waterfall, Database.